Exploring the Use of Various Board Games to Enhance Speaking Skills Viewed from Students’ Phonology Awareness: Speaking Skills; Phonology Awareness; Games - Heri Hidayatullah; Haerazi Haerazi (Journal of Language and Literature Studies, 2021)
Speaking skill is classified as a productive skill after writing skills. It is related to communicative performance dealing with phonetic, fluency, accuracy, pronunciation, grammatical competence, intonation, and vocabulary mastery. Besides, students’ phonology knowledge is crucial in understanding speakers’ utterances in speaking activities. Therefore, students’ phonology awareness in speaking classes determine the students are success or not in having speaking skills. This study aims to elaborate the use of speaking board games to improve students’ speaking skills viewed from phonology awareness. To attain the research aims, this study employed classroom action research. The problems are focused on students’ speaking skills in relation to phonology awareness. The research data are classified into qualitative and quantitative data. The qualitative data were gained using interview and observation sheets, while the quantitative data were collected using speaking tests. Based on the research findings, this study can be concluded that the use of speaking board games in teaching speaking classes which was combined with other various materials was able to improve students’ confidence and critical thinking skills to speak. It helped students practice their fluency, practice their accuracy, and gave smooth correction to the grammatical errors being made. Providing students with various speaking practices, the use of board games also facilitated students to improve their pronunciation inside and outside classes, vocabulary, and engage them to learn the English daily expressions in various topics.